Women in the coffee supply chain: Identifying challenges and opportunities in San Francisco de Opalaca and La Paz, Honduras - Soto, Fernanda; Rodriguez, Rene; Gonzalez, Silvia (2025)
Companies face challenges despite the growing interest in investing in and measuring gender equality and women's empowerment within supply chains. For one, they may be unclear about the tools that best fit their needs, given the number of frameworks, approaches, and tools that currently exist to support gender integration and programming (Mora et al., 2023). Another challenge is to better understand who are the various actors, women, and marginalized groups, involved in their supply chain. Currently, the lack of data—and specifically data that would allow us to know the different groups of women involved in the chain—makes it difficult to: a. Understand women’s livelihoods, the diverse roles they play in supply chains, and the barriers to improving their performance in these chains. b. Define actions aimed at increasing the benefits they could obtain from the chain (including economic empowerment). c. Initiate adaptive learning within companies to achieve sustainable supply chains in different social and productive (or business) contexts.